Incidence and outcomes of uterine rupture in women with unscarred, preterm or prelabour uteri: data from the international network of obstetric survey systems - Vandenberghe, G; Vierin, A; Bloemenkamp, K; Berlage, S; Colmorn, L; Deneux-Tharaux, C; Donati, S; Gissler, M; Knight, M; Langhoff-Roos, J; Lindqvist, PG; Maier, B; et al. (Wiley, 2023)
Objective Analysis of atypical cases of uterine rupture, namely, uterine rupture occurring in unscarred, preterm or prelabour uteri.